Sistem Perekrutan Pegawai Menggunakan Microsoft Excel: Studi Kasus: Badan Kepegawaian & Sumber Daya Manusia - Randi Tandiele; Kristia Yuliawan (Jurnal Teknologi dan Informatika, 2024)
This application is an innovative solution that uses Microsoft Excel as the main platform to facilitate the employee recruitment process in companies. With a focus on efficiency and ease of use, this application provides various features that support complete management from start to finish of the recruitment process. The main features of this application include neatly structured candidate data management in Excel spreadsheet format. This allows HR and recruiting teams to easily manage important information such as resumes, educational history, work experience, as well as interview and test notes. In addition, this application is equipped with a data-based evaluation tool that allows companies to identify candidates who best suit the needs of the available positions. The use of Excel formulas and analytical features helps in making smarter and more informed hiring decisions. Integration with email allows candidates to be sent notifications regarding the status of their applications automatically, improving transparency and applicant experience. An interactive analytical dashboard is also provided to monitor and analyze the effectiveness of recruitment strategies in real-time. With a combination of the reliability of Microsoft Excel as a data analysis tool and extensive customization capabilities, this application is designed to optimize the employee recruitment process, increase operational efficiency, and reduce the time needed to fill vacant positions.